2011
DOI: 10.1007/s00520-011-1180-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the incidence of delayed nausea and vomiting in patients with colorectal cancer receiving oxaliplatin-based chemotherapy

Abstract: The use of a 5-HT(3) antagonist and dexamethasone prior to oxaliplatin results in excellent control of nausea and vomiting (CR-90%) during the 24 h after chemotherapy. However, without further antiemetic treatment, complete response in the delayed period decreased to 54%. This study supports the need for routine antiemetic prophylaxis for delayed nausea and vomiting following oxaliplatin-based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“… 20 Another prospective trial found that in patients with colorectal cancer receiving FOLFOX chemotherapy, standard prophylaxis prevented 90% of CINV in the first 24 h, but after 5 days of follow-up, this value decreased to 54% due to delayed nausea and vomiting. 21 A number of studies have shown that 5-HT3 RA provides better control of CINV in the acute phase, but it is less effective in preventing CINV in the delayed phase. 22 Because of the poor control of delayed vomiting caused by MEC in the dual drug regimen, for this group of patients, we need to explore more drug combinations to better control delayed nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Another prospective trial found that in patients with colorectal cancer receiving FOLFOX chemotherapy, standard prophylaxis prevented 90% of CINV in the first 24 h, but after 5 days of follow-up, this value decreased to 54% due to delayed nausea and vomiting. 21 A number of studies have shown that 5-HT3 RA provides better control of CINV in the acute phase, but it is less effective in preventing CINV in the delayed phase. 22 Because of the poor control of delayed vomiting caused by MEC in the dual drug regimen, for this group of patients, we need to explore more drug combinations to better control delayed nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…To date there have been few studies in the cancer population of the impact of telecommunication-based devices that regularly collect data from patients at home and transmit the results to a healthcare professional for response in real-time. Given the distressing and serious side-effects that are common during and following cancer treatments 2 21 this is surprising given the apparent cost-effectiveness of these systems in chronic disease patients. This review aimed to identify papers that not only described remote monitoring systems in cancer patients, but also statistically analyzed patient clinical and health care system outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…nausea, vomiting, mucositis, diarrhea and febrile neutropenia). 2 11 While some side-effects, such as fatigue and mucositis, are not in themselves life threatening, they are associated with poorer treatment compliance, impaired quality of life, and increased infections and time spent in hospital. 12 14 Fatigue also has a significant impact on patient quality of life and is associated with mood disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of delayed CINV has been studied best in chemotherapy regimens containing high-dose cisplatin or anthracyclines and cyclophosphamide (AC) combinations. However, delayed CINV is also associated with moderately emetogenic chemotherapy (non-AC MEC) regimens [ 5 10 ]. Non-AC MEC consists of a broad range of chemotherapeutic agents, with emetogenic potentials of 30 to 90 %; agents like oxaliplatin and irinotecan have an emetogenic potential in the lower part of this range, as opposed to carboplatin, which is at the high end [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%